Initiation of Z-fract Formula as a Bio-additive for Industrial Machine Efficiency Inisiasi Z-fract Formula sebagai Bio-aditif Efisiensi Mesin Industri - Fitri, Noor; Mauludiyah, Riskiyatul; Sukri, Qomarudin; Syahputra, Rahmat; Nurhuddah, Ika Ila (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Since the onset of the industrial revolution, fuel oil (BBM) has served as the primary energy source. In Indonesia, there was a 10 percent increase in fuel consumption in 2016, reaching 48.6 million m3/year compared to the previous year, 2015. However, this rise in fuel usage hasn't been matched by an increase in Indonesia's oil reserves, which are estimated to deplete by 2050. With limited fuel reserves and mounting concerns about global warming and environmental pollution, extensive exploration into renewable and sustainable alternative fuels has been undertaken. Various researchers have proposed solutions, one of which involves incorporating additives derived from abundant non-edible natural resources in Indonesia, such as essential oils. Essential oils are extracted from plant parts using diverse techniques. These oils possess a low vapor point and are soluble in diesel fuel. Moreover, they contain diverse chemical compounds with oxygen atoms, enabling them to enhance the combustion process in diesel engines. Acting as bioadditives, essential oils augment the quality of diesel fuel. Fuel additives, which are substances added to fuel—especially gasoline or diesel—aim to enhance fuel properties, leading to improved performance. Their incorporation can reduce detrimental emissions like hydrocarbons (HC), particulate matter, CO2, and NOx emissions. Furthermore, they aid in increasing fuel viscosity, anti-knock properties, octane and cetane ratings, as well as improving cold flow characteristics, thermal stability, cleanliness, and preventing engine corrosion. Research outcomes indicate that essential oils can decrease diesel fuel consumption, lower gas emissions, and safeguard engines from rust deposits. Citronella essential oil stands out as a potential bioadditive due to its main compounds—citronellal, geraniol, and citronellol—that contain oxygen atoms. PT Arutmin Kintap has supported local farmers and distillers by cultivating citronella on 10 hectares of former mining land. Their plan involves utilizing the produced citronella essential oil to create the Z-fract Formula as a Bio-additive for industrial machine efficiency, collaborating with the Indonesian Islamic University (UII). The Z-fract bio-additive formula is specifically designed for PT Arutmin's industrial machines. Key strategic actions include: (1) Conducting workshops for essential oil farmers on proper planting techniques aligned with Good Agricultural Practices (GAP) to ensure raw material availability and production of citronella essential oil meeting SNI standards; (2) Characterization of citronella oil produced in Kintap; (3) Fractionating citronella essential oil; (4) Analysis of the chemical composition of the citronella oil fraction.